The Effect of Ethanol Percentage on Antioxidant Activity of Celery (Apium graveolens) - Lukman, Lukman; Mus, Suwahyuni (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Excessive physical activity forms reactive oxygen species (ROS), which oxidize low-density lipoprotein (LDL) and trigger the formation of arteriosclerosis. Increasing antioxidant consumption, such as celery (Apium graveolens), has been proven to prevent heart disease. This study investigated the effect of ethanol concentration on the antioxidant activity of celery herbs in vitro and in vivo. The dried herb was macerated using a mixture of ethanol and water (100% water, 50% ethanol, 70% ethanol, 90% ethanol, and ethanol absolute (99,5%)). Antioxidant activity was determined using the LDL oxidation and β-carotene bleaching methods. Additionally, the antioxidant in vivo activity was carried out on rats using the high-intensity swimming exercises method. The results showed that 70% ethanol extract was significantly (p<0.05) able to inhibit the degradation of β-carotene and LDL oxidation compared to other extracts. The 70% ethanol extract also reduced malondialdehyde levels (14.35±0.63 ng/mL) compared to negative controls (46.04±1.69 ng/mL). In addition, there was an increase in glutathione levels after administration of 70% ethanol extract (111.93±11.68 ng/mL) compared to negative controls (46.04±1.69 ng/mL). In conclusion, 70% ethanol extract of celery herb has the potential to be developed as an alternative to prevent arteriosclerosis.